Risk Analysis of Joint Operation Implementation on Large Dam Projects (Case Study: Tapin Dam) - Septian Rizki Pramono; Tri Joko Wahyu Adi (International Journal Labs, 2023)
Along with the implementation of project work with the Joint Operation (KSO) system, there are risks that arise due to differences in vision between partners so that risks that may occur need to be identified so that risk mitigation can be carried out. This study aims to identify the risks that arise in the KSO project in Tapin Dam, South Kalimantan. KSO risk identification begins with conducting a literature study to create a risk list and then conducting a preliminary survey and expert validation to determine the relevance of KSO risk to the project that is the object of research. Furthermore, the Probability Impact Matrix (PIM) is used to see the dominant risks that affect the achievement of project goals. This study also analyzes the risk allocation of each party and proposes mitigation actions. Based on the results of the study, it was found that among 30 relevant risk variables, 11 variables identified as high risk which are then allocated and determined its risk mitigation.